1917 Ill. Laws 341 - (:unkn) unknown (My University, 1917)
An Act to Define and Provide a Punishment for the Crime of Burglary with Explosives, § 1: Enhanced the sentence of anyone who breaks and enters into a building with the purpose of committing any crime and uses nitro-glycerine, dynamite, gunpowder, or any other explosive. Violators deemed guilty of burglary with explosives and shall be imprisoned not less than five nor more than twenty years.
Keywords: USE OF EXPLOSIVES WHILE COMMITTING A CRIME